'Going beyond the Troika': Power and discourse in Portuguese austerity politics. (19th January 2017) - MOURY, CATHERINE; STANDRING, ADAM
Abstract: This article analyses the margin of manoeuvre of Portuguese executives after the onset of the sovereign debt crisis in 2010–2015. To obtain a full understanding of what happened behind the closed doors of international meetings, different types of data are triangulated: face‐to‐face interviews; investigations by journalists; and International Monetary Fund and European Union official documents. The findings are compared to the public discourse of Prime Ministers José Sócrates and Pedro Passos‐Coelho. It is shown that while the sovereign debt crisis and the bail‐out limited the executive's autonomy, they also made them stronger in relation to other domestic actors. The perceived need for 'credibility' in order to avoid a 'negative' reaction from the markets – later associated with the conditions of the bail‐out – concurrently gave the executives a legitimate justification to concentrate power in their hands and a strong argument to counter the opponents of their proposed reforms. Consequently, when Portuguese ministers favoured policies that were in congruence with those supported by international actors, they were able to use the crisis to advance their own agenda. Disagreement with Troika representatives implied the start of a negotiation process between the ministers and international lenders, the final outcome of which depended on the actors' bargaining powers. These strategies, it is argued, constitute a tactic of depoliticisation in which both the material constraints and the discourse used to frame them are employed to construct imperatives around a narrow selection of policy alternatives.